Assessment of Pregnancy Outcome in Gestational Diabetes Milletus Patient in Maternity Teaching Hospital in Sulaimani City - Ismael, Niyan Hakem; Fars, Gona Othman; Abdulkarim, Awayi Xazy (Sulaimani Journal for Pure and Applied Sciences, 2016)
The current study was undertaken to assess of pregnancy outcome in gestational diabetes milletus patient. This study was carried out for the period of 10th March to 12th May of 2014, sample of (100) pregnant women who have been attended the maternity teaching hospital in Sulaimani city, to identify the assessment of pregnancy outcome in Gestational Diabetes Milletus and explore association between some sociodemographic characteristic of the sample baby outcome and reproductive history, the results show that there is a strong association between reproductive history and Gestational Diabetes Milletus.
Keywords: GDMMaternal outcomeBaby outcome